Sistem Pendukung Keputusan dalam Pemilihan Motor Matic Menggunakan Metode Preference Selection Index (PSI) - Afiq Alghazali Lubis; Josua Pinem; Muhammad Agus Syaputra (LPPM STIKI MALANG, 2024)
This research aims to design a Decision Support System for selecting automatic motorbikes using the Preference Selection Index (PSI) Method. In the midst of the rapid development of the automotive industry, especially automatic motorbikes, the PSI method is applied without weighting criteria to help consumers choose motorbikes based on five main criteria. By normalizing data according to the type of cost or benefit criteria, the PSI method offers a simple and effective solution in decision-making processes involving various criteria. The system developed is expected to be able to provide recommendations for automatic motorbikes that suit the user's preferences and needs. The challenge in choosing an automatic motorbike lies in the complexity of considering various important criteria for consumers, such as price, completeness of documents, year of manufacture, condition and authenticity of spare parts. Therefore, this research aims to develop a decision support system that can provide effective motorbike recommendations based on these criteria without weighting. The PSI method is applied to achieve this goal by normalizing data according to the type of cost or benefit criteria, so that it is hoped that the resulting solution can meet the user's preferences and needs in choosing an automatic motorbike.